Is It True That Job Satisfaction and Work Environment Affect Employee Turnover Intention? - Abdullah, Fariz; Djunawan, Achmad; Rizki, M Risya (Jurnal Multidisiplin West Science, 2025)
The turnover of medical support employees at Hospital X Surabaya in 2023 was above the standard (10.8%). The high turnover of medical support employees can cause losses for the hospital because they have to spend money on recruitment, orientation, and training. This study aims to analyze the effect of the work environment and job satisfaction on the turnover intention of medical support employees at Hospital X Surabaya. This type of research is quantitative analytical with a cross-sectional research design. The population in this study was 65 medical support employees at Hospital X Surabaya. The sample calculation used a simple random sampling technique that obtained a sample of 40 employees. This study used ordinal logistic regression. The results of the study showed that the work environment and job satisfaction had a significant influence on the turnover intention of medical support employees at Hospital X Surabaya.